Golden jackal (Canis aureus L., 1758) – a new species in the theriofauna of Belarus - Grichik, Vasilij V.; Prakapchuk, Vadzim V.; Grebenchuk, Alexandra E.; Rabtsava, Alina A.; Tsybovsky, Iosif S. (Experimental Biology and Biotechnology, 2019)
Continuing in Europe, the settlement of the golden jackal (Canis aureus) over the last decade has covered the territory of the Republic of Belarus. The article has 6 reliable facts this species registration in 2011–2018 in the southern and south-western parts of the country, north to the line Kobrin – Soligorsk – Bobruisk. In 2 cases, the animals were spotted visually or by voice, in the remaining 4 – shot by hunters. Species identification of the three individuals are confirmed by photographs and molecular-genetic studies, the skull and skin are collected from the other one. The photos and measurements of the skull (from an adult male) are presented, the phenotype features of adults in the autumn-winter period and biotopes in which these animals are encountered are briefly discussed. Most of the meetings are timed to semi-open meliorated territories with shrub thickets and ameliorative canals.
Keywords: golden jackal Canis aureus; resettlement in Europe; theriofauna of Belarus